Memorization in a Foreign Language: The Role Semantic Memory in Quran Memorization (Khairulummah, 2023)
Literature suggests that phonological memory on its own would be inadequate because it is associated with short term memory STM. Information encoded phonologically is of limited duration and capacity. Taking the nature and working of working/phonological memory into account, it can be assumed that people memorizing text in a foreign language might not be deploying working/phonological memory to help them internalise the text. However, if it is assumed that the text memorized in a foreign language ends up in LTM, how does information get encoded there, and does memorization in foreign language meet the conditions for LTM storage, as typically understood in the research literature? This paper looks at the role of semantic memory and examines the nature and status of information in there with reference to some models of long term memory in relation to Quran memorization by non-Arabic speaking memorizers. We explore the process of memorization and ask whether the Quran text ends up as part of the memorizers’ integrated knowledge in long term semantic memory.
Keywords: Literature; suggests; phonological; inadequate; memorizing